Qihuang needle therapy in senile cervical spondylotic radiculopathy - Yang, Juan; Huang, Hongfang; Shi, Jinshan; He, Cheng; Zhang, Kun; Chen, Zhenhu; Zeng, Rui; Liu, Jia (Frontiers in Aging Neuroscience, 2023)
Background：Neurogenic cervical spondylosis (CSR) accounts for approximately 50%-60% of all types of cervical spondylosis, and its incidence is the highest. To investigate clinical efficacy of Qihuang needle in senile cervical radiculopathy treatment. Methods Fifty-five elderly patients with neurogenic cervical spondylosis were divided into general acupuncture group (27 cases) and the Qihuang acupuncture group (28 cases) randomly, The treatment lasted for 3 sessions, and the VAS scores and the Tanaka Yasuhisa scale were compared before treatment, after the first treatment, after the first session, and at the end of the session. Results The basic data of the two groups before treatment have no difference. After the first consultation, after first course of treatment, and at end of treatment course, the VAS scores in mackerel acupuncture group decreased significantly and Tanaka Kangjiu scale scores increased significantly. The efficiency rate of first and second course of treatment was significantly higher in Qihuang acupuncture group than control group. Conclusion Qihuang needle therapy is recommended for the cervical spondylosis treatment of nerve root type. Guided by the theory of meridians and tendons, the meridians and tendons are selected to gather at the local acupoints of the joints. It has the characteristics of less acupoint selection, quick operation and no needle retention..